Peningkatan Keterampilan Membaca Pemahaman Menggunakan Strategi PORPE (Predict, Organize, Rehearse, Practice, Evaluate) pada Peserta Didik Kelas IV SDN 12 Cimparuh Kota Pariaman - Arumdati, Arumdati; Suriani, Ari; Sukma, Elfia; Meizatri, Ranti (TSAQOFAH, 2025)
This research is motivated by the low reading comprehension skills of grade IV students of SDN 12 Cimparuh Pariaman City which is caused by the fact that in the learning process students are not accustomed to memorizing reading texts. Students are just reading without understanding more deeply the content of the text they read. The purpose of this study was to describe the improvement of reading comprehension skills using the PORPE (Predict, Organize, Rehearse, Practice, Evaluate) strategy in grade IV students of SDN 12 Cimparuh Pariaman City. The subjects of this study are teachers and students of grade IV of SDN 12 Cimparuh Pariaman City. The approach used is a qualitative and quantitative approach. The type of research used is class action research (PTK) which is carried out in two cycles, namely cycle I consisting of 2 meetings and cycle II consisting of 1 meeting. Data collection techniques are in the form of tests and non-tests. The results of the study showed that in the first cycle of the pre-reading stage, an average score of 78.47 was obtained with a sufficient predicate and increased in the second cycle to 90.27 with a very good predicate. The reading stage in the first cycle obtained an average score of 72.22 with a sufficient predicate and increased in the second cycle to 84.72 with a good predicate. The post-reading stage in the first cycle obtained an average score of 72.91 with a sufficient predicate and increased in the second cycle to 86.11 with a good predicate. Based on the results of the study, it can be concluded that using the PORPE (Predict, Organize, Rehearse, Practice, Evaluate) strategy can improve the reading comprehension skills of grade IV students of SDN 12 Cimparuh Pariaman City.